Christian Digital Literacy: A Preschool-Teen Learning Model for Faith Formation in the 4.0 Era - Darmawan, Diki (Hikmat : Jurnal Agama Kristen, 2025)
The 4.0 era places early childhood to adolescence in a digital ecosystem that shapes mindsets, habits, and practices of faith. This study developed and tested a cross-level Christian Digital Literacy Model (PAUD–SMA) based on a spiral curriculum that integrates four pillars: (1) digital competencies (access, analysis, creation, collaboration), (2) practical theology with a biblical narrative lens (creation–fall–redemption–restoration), (3) digital spiritual disciplines (short prayers, digital sabbaths, media examinations), and (4) compassionate digital citizenship. Using a mixed-methods approach within a Design-Based Research framework (co-design → prototype → pilot → randomized quasi-experimental field test per class), data were collected through literacy/disposition/practice scales, situational tests, digital artifact rubrics, fidelity observations, LMS logs, and FGDs/reflective journals. Results indicate significant improvements in cognitive (faith-based digital literacy), affective (compassion, discourse civility, citation honesty), and practical (digital sabbath habits and media examination), with medium to high effect sizes for cognitive and medium for affective–practical. Micro-liturgical practices served as habitus-forming mechanisms that sustained habit retention into short-term follow-up, while home–school–church collaboration strengthened the transfer of virtues to contexts beyond the classroom. Artifacts/portfolios demonstrated improvements in content quality, honest citations, and compassionate counter-speech practices. The research concludes that digital spaces are effectively positioned as spaces for faith formation, not simply distribution channels. The resulting model, assessment tools, and parenting guidance are ready for replication with contextual adaptations, while regular reinforcement sessions and longitudinal studies are recommended to assess the resilience of habits in the medium to long term.